Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174091
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Computing in Special Needs Classrooms

Abstract: With a growing call for an increased emphasis on computing in school curricula, there is a need to make computing accessible to a diversity of learners. One potential approach is to extend the use of physical toolkits, which have been found to encourage collaboration, sustained engagement and effective learning in classrooms in general. However, little is known as to whether and how these benefits can be leveraged in special needs schools, where learners have a spectrum of distinct cognitive and social needs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Based on the research results; it can be indicated that coding education can provide many educational opportunities to support the problem-solving skills of special education students. Some of these opportunities are the ability to break down problems into smaller parts and to draw on both logic and creativity to figure out the best ways to solve them (Lechelt et al, 2018). To inform and educate the future generation, companies, universities should make investments and serious ventures for coding and robotic applications education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research results; it can be indicated that coding education can provide many educational opportunities to support the problem-solving skills of special education students. Some of these opportunities are the ability to break down problems into smaller parts and to draw on both logic and creativity to figure out the best ways to solve them (Lechelt et al, 2018). To inform and educate the future generation, companies, universities should make investments and serious ventures for coding and robotic applications education.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that especially unplugged coding activities will appeal to a much wider group of students with having different disabilities. Lechelt et al (2018), in their research, found out that a physical toolkit (magic cube) could be used both supporting comprehensions of computational concepts and enabling students to get excited about learning with fun. Because of these, computer-aided coding activities may only address students having computer usage skills.…”
Section: Research Questionsmentioning
confidence: 99%
“…Verbally define physical sensors and sensing at the beginning of the session, with examples, to introduce the children to the concepts that they would be using during the exploratory activities. In steps 2 and 3 of the sessions, we used the Magic Cubes toolkit [18,39] to enable the children to explore and visualize sensor data (see Figure 2). The Magic Cubes are Arduinobased, wireless, hand-sized interactive cubes that contain a number of different embedded sensors.…”
Section: The Studiesmentioning
confidence: 99%
“…The Magic Cubes are Arduinobased, wireless, hand-sized interactive cubes that contain a number of different embedded sensors. The cubes can be used to visualize sensor readings, and can be grasped, carried and shared easily, and in so doing encourage experimentation while exploring data [16,18]. Five different sensors were used with the cubes, for measuring the human body or environment (see Table 1).…”
Section: The Studiesmentioning
confidence: 99%
See 1 more Smart Citation